2000
DOI: 10.1017/s0022029900004301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heat and pressure treatments of skim milk, fortified with whey protein concentrate, for set yogurt preparation: effects on milk proteins and gel structure

Abstract: Heat (85 degrees C for 20 min) and pressure (600 MPa for 15 min) treatments were applied to skim milk fortified by addition of whey protein concentrate. Both treatments caused > 90 % denaturation of beta-lactoglobulin. During heat treatment this denaturation took place in the presence of intact casein micelles; during pressure treatment it occurred while the micelles were in a highly dissociated state. As a result micelle structure and the distribution of beta-lactoglobulin were different in the two milks. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 1 publication
12
94
1
4
Order By: Relevance
“…Extensive denaturation (i.e., 91.4%) was evident after pressure treating WPI at 700 MPa which was comparable to, although slightly lower than, that caused by heating at 78 o C × 30 min (i.e., 93.7%). These results are comparable to those of Needs et al [26] who reported that both heat (80 o C × 20 min) and pressure (600 MPa × 15 min) treatments caused > 90% denaturation of β-lactoglobulin in skim milk. In an earlier study, Van Camp et al [40] found that the amount of native β-lactoglobulin in WPC was reduced significantly after pressurisation at 400 MPa for 30 min, in contrast to α-lactalbumin, for which no major changes were evident.…”
Section: Resultssupporting
confidence: 89%
“…Extensive denaturation (i.e., 91.4%) was evident after pressure treating WPI at 700 MPa which was comparable to, although slightly lower than, that caused by heating at 78 o C × 30 min (i.e., 93.7%). These results are comparable to those of Needs et al [26] who reported that both heat (80 o C × 20 min) and pressure (600 MPa × 15 min) treatments caused > 90% denaturation of β-lactoglobulin in skim milk. In an earlier study, Van Camp et al [40] found that the amount of native β-lactoglobulin in WPC was reduced significantly after pressurisation at 400 MPa for 30 min, in contrast to α-lactalbumin, for which no major changes were evident.…”
Section: Resultssupporting
confidence: 89%
“…Acid gels obtained from high-pressure homogenized milk showed a linear decrease in whey holding capacity and retention of more than 20% whey after centrifugation for 25 min (Hernandez and Harte 2008). Similarly, Needs et al (2000) recorded lower values of fracture stress in set yoghurts made from pressure treated milk (60 MPa for 15 min) compared to heat treated milk. Yoghurt prepared from milk that was ultra high pressure homogenized at 200 and 300 MPa at 30 and 40°C considering modifications induced in the fat fraction that could delay the lipid oxidation and lower the degree of lipolysis, resulted in expected results (Serra et al 2008).…”
Section: Application Of Hhp In Dairy Industrymentioning
confidence: 89%
“…They observed that milk subjected to HHP treatment and thermal treatment followed by HHP, loses its white colour and turns yellowish. This might be due to reduction in size of casein micelles (Needs et al 2000). Whereas milk when first subjected to HHP followed by thermal treatment regained its whitish colour and this may be attributed to reversible nature of casein micelles (or reaggregation of disrupted micelles) towards HHP treatment when applied in the range of 300-676 MPa followed by thermal treatment.…”
Section: Application Of Hhp In Dairy Industrymentioning
confidence: 98%
“…This advanced Maillard reaction may have additional undesirable consequences for nutrition (Kilshaw et al, 1982;Adrian, 1974;Rigo et al, 1994). The FAA composition or bioavailability in formulas may also be altered during processing and enzymatic hydrolysis (Donovan and Lonnerdal, 1989;Recio and Olieman, 1996;Needs et al, 2000).…”
Section: Discussionmentioning
confidence: 99%